(untitled) (Filološke pripombe, 2019)
In the context of variational (quantitative) sociolinguistics the object of research is revealing statistical regularities of speech depending on any social factors. Such approach makes possible to consider sociolect as the probabilistic function from one (particular sociolect) or several (generalized sociolect) social variables. In the article the realization of particular and generalized sociolects is shown on a material of Perm regiolect pronunciations.